A Simple Kit of Plate-Trapped Antigen Enzyme-Linked Immunosorbent Assay for Identification of Plant Viruses - Nascimento, Aline Kelly; Lima, José Albersio; Barbosa, Graziela (Revista Ciência Agronômica, 2016)
Many methods can be used for arriving in a correct virus disease diagnose, and the serological techniques are the most used methods for plant virus identification. The indirect enzyme-linked immunosorbent assay (Indirect-ELISA) or plate-trapped antigen ELISA (PTA-ELISA) has been useful for detection of viruses in a wide range of situations, especially to test a large number of samples in a relatively short period of time. Immune-biological Companies have developed practical kits for direct ELISA or double antibody sandwich (DAS-ELISA), but neither Company has developed kits for PTA-ELISA. As a single universal antibody-conjugate is used for detection of a wide range of plant viruses, the PTA-ELISA technique is more economical, practical and suitable for virus detection. Considering also the great problem of including infectious plant viruses in DAS-ELISA kits, a simple kit for PTA-ELISA was developed for plant virus identification. Extracts from infected plant tissues were added into the ELISA plate wells, which were sealed with plastics and maintained in the refrigerator and Laboratory conditions for different periods of time. The plates were tested by the regular PTA-ELISA and after 20 months of incubation, the plate showed excellent results when used for detection of six virus species from the genera Comovirus, Cucumovirus, Potyvirus and Sobemovirus in infected plant tissues. The ELISA plate trapped virus together with its specific antiserum could constitute a simple kit, which will permit the exchange of antisera among virologists without transferring infectious viruses from one laboratory to another to be used as control.